PENGEMBANGAN WEB SEMNAS IKRA-ITH DENGAN METODE WDLC (WEB DEVELOPMENT LIFE CYCLE) - Dermawan, Indra; Purtiningrum, Susi Wagiyati; Budilaksono, Sularso; Suwarno, Muhammad Anno (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
At this time, a way to improve insight in a field can be by reading books, watching television, attending exhibitions, visiting museums. Another way that is currently often used to add insight is to attend a seminar, both seminars with national and international scales. With the rapid development of technology and now almost advanced technology systems putting forward online as one of the ways of accessibility in meeting every need, Persada Indonesia University YAI makes an innovative idea of creating a web system to register national scale seminar registration with various technology topics which can be followed by anyone. In the web there will also be various kinds of competitions that can be followed by various teams and visits to large industries that certainly add to the insight.